Romanticism and Modern Fiction - Rothbard, Murray N. (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2015)
In this essay, the author elaborates a criticism of modern fiction and analyzes the romantic artist as one that brings to the fore ideal values that man can strive to achieve. Concentrating his analysis on Ayn Rand’s novel Atlas Shrugged, the author argues that this work is a significant example of romantic fiction that presents values that could be implemented, while presenting an explicit philosophical content.